2021
DOI: 10.1371/journal.pgen.1009174
|View full text |Cite
|
Sign up to set email alerts
|

Phase-related differences in egg production of the migratory locust regulated by differential oosorption through microRNA-34 targeting activinβ

Abstract: Outbreaks of locust plagues result from the long-term accumulation of high-density egg production. The migratory locust, Locusta migratoria, displays dramatic differences in the egg-laid number with dependence on population density, while solitarious locusts lay more eggs compared to gregarious ones. However, the regulatory mechanism for the egg-laid number difference is unclear. Herein, we confirm that oosorption plays a crucial role in the regulation of egg number through the comparison of physiological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…The fluorescence results indicated that miRNA-novel-53 and ModSP are both localized in the cytoplasm. These results are similar to those of previous studies showing that miRNA and its target gene both play roles in the cytoplasm [ 58 , 59 ]. Mature miRNA-novel-53 is transported into the cytoplasm to inhibit the translation of ModSP transcripts and downregulate its expression level.…”
Section: Discussionsupporting
confidence: 92%
“…The fluorescence results indicated that miRNA-novel-53 and ModSP are both localized in the cytoplasm. These results are similar to those of previous studies showing that miRNA and its target gene both play roles in the cytoplasm [ 58 , 59 ]. Mature miRNA-novel-53 is transported into the cytoplasm to inhibit the translation of ModSP transcripts and downregulate its expression level.…”
Section: Discussionsupporting
confidence: 92%
“…The high expression of Ago1 in the ovary and Gawky in the head implies that these genes play important roles in these tissues. Previous studies have shown that Ago1 is highly expressed in Drosophila oocytes, while in B. mori , it is mainly expressed in the ovary, testis, midgut, and head ( Wu et al, 2021 ; Yang et al, 2021 ; Zhao et al, 2021 ). These various expression patterns may be due to the specific functions of Ago1 genes in different insect species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that miR‐34 was upregulated during sexual maturation in the fat body of B. dorsalis , indicating that it was possibly involved in reproductive development. Interestingly, miR‐34 plays distinct roles in different insect species, including wing polyphenism, 57 larval growth and wing morphogenesis, 58 oosorption 59 etc. These studies suggest that miRNAs differ in their reproductive roles among different species.…”
Section: Discussionmentioning
confidence: 99%